Integrated Uncertainty in Knowledge Modelling and Decision Making International Symposium, IUKM 2011, Hangzhou, China, October 28-30, 2011, Proceedings - Tang, Yongchuan; Huynh, Van-Nam; Lawry, Jonathan (Lecture Notes in Artificial Intelligence,, 2011)
This book constitutes the refereed proceedings of the International Symposium on Integrated Uncertainty in Knowledge Modeling and Decision  Making, IUKM 2011, held in Hangzhou, China, in October 2011. The 21 revised full papers presented together with 1 keynote lecture and 5 invited talks were carefully reviewed and selected from 55 submissions. The papers provide a wealth of new ideas and report both theoretical and applied research on integrated uncertainty modeling and management.